The economic value of liquid biopsy for genomic profiling in advanced non-small cell lung cancer. (July 2022) - Ezeife, Doreen A.; Spackman, Eldon; Juergens, Rosalyn A.; Laskin, Janessa J.; Agulnik, Jason S.; Hao, Desiree; Laurie, Scott A.; Law, Jennifer H.; Le, Lisa W.; Kiedrowski, Lesli A.; Melosky, Barbara; Shepherd, Frances A.; et al.
Background: Liquid biopsy (LB) can detect actionable genomic alterations in plasma circulating tumor circulating tumor DNA beyond tissue testing (TT) alone in advanced non-small cell lung cancer (NSCLC) patients. We estimated the cost-effectiveness of adding LB to TT in the Canadian healthcare system. Methods: A cost-effectiveness analysis was conducted using a decision analytic Markov model from the Canadian public payer (Ontario) perspective and a 2-year time horizon in patients with treatment-naïve stage IV non-squamous NSCLC and ⩽10 pack-year smoking history. LB was performed using the comprehensive genomic profiling Guardant360™ assay. Standard of care TT for each participating institution was performed. Costs and outcomes of molecular testing by LB + TT were compared to TT alone. Transition probabilities were calculated from the VALUE trial (NCT03576937). Sensitivity analyses were undertaken to assess uncertainty in the model. Results: Use of LB + TT identified actionable alterations in more patients, 68.5 versus 52.7% with TT alone. Use of the LB + TT strategy resulted in an incremental cost savings of 3065 CAD per patient (95% CI, 2195–3945) and a gain in quality-adjusted life-years of 0.02 (95% CI, 0.01–0.02) versus TT alone. More patients received chemo-immunotherapy based on TT with higher overall costs, whereas more patients received targeted therapy based on LB + TT with net cost savings. Major drivers of cost-effectiveness were drug acquisition costs and prevalence of actionable alterations. Conclusion: The addition of LB to TT as initial molecular testing of clinically selected patients with advanced NSCLC did not increase system costs and led to more patients receiving appropriate targeted therapy.